Contenido del carbono en los productos y residuos forestales generados por el aprovechamiento y el aserrio en la reserva de Biosfera Maya - Bamaca Figueroa, E.; Kanninen, M.; Louman, Bastian; Pedroni, L.; Gómez, M. (2004)
The use and industrial transformation of timber from tropical natural forests produce big quantities of wood residues that generate emissions of carbon dioxide (CO2) when burned or decayed. The greenhouse effect is mainly produced by CO2 emissions. Carbon content in wood residues was evaluated in the forest management unit Rio Chanchich, Peten, Guatemala. Wood volume per individual and the biomass damaged by felling of each tree were estimated for 57 trees (4,5% of the trees cut). Biomass eliminated by road and stockyard construction was estimated according to size of the cleared area. Useful volume and residues from 95 wood logs were estimated at the sawmill. Average volume per individual was 6,24 m3. Only 53,3% of the wood arrived at the sawmill while the rest remained as residues in the forest. From that amount, 87% was timber; milling efficiency was 51,2%, using a portable sawmill. In terms to carbon, logging removed 10,2 tC/ha from the forest, but only 1,4 tC/ha (13,7%) ended up in wood products.